BODY FAT DISTRIBUTION CHANGES DURING WEIGHT LOSS DETERMINED BY DUAL-ENERGY X-RAY ABSORPTIOMETRIC TRUNK/ TOTAL RATIOS AS INDEXES OF ABDOMINAL OBESITY - Shubeska Stratrova, Slavica; Spasovski, Dejan; Velikj Stefanovska, Vesna (SHMSHM / AAMD, 2019)
Objective. The effect of weight loss on body fat distribution was examined through the trunk/total tissue and fat mass ratios, indexes of central, abdominal obesity determined by dual-energy X-ray absorptiometry (DXA). Material and methods. Following parameters were determined before and after weight loss: body mass index (BMI), body weight (BW), total and trunk fat mass (FM) and its percent (FM%), tissue mass (TM) and TM fat percent (TMf%) with DXA as well as DXA indexes of abdominal body fat distribution: trunk/total FM (Tr/To FM) and Tr/To FM%, trunk/total TM (Tr/To TM) and trunk/total TMf% (Tr/To TMf%) in two overweight subjects. Results. BW of 62.9±1.2 kg and BMI value of 28.98±0.78 kg/m2 before the weight loss lowered to 49.96±1.3 kg (p<0.012) and normal BMI 22.81±0.62 kg/m2 (p<0.012). Tr/To TMf% value decrease from 1.02±0.01 to 0.97±0.03 was significant (p<0.013) and Tr/To FM% value decrease from 1.04±0.01 to 0.99±0.02 was also significant (p<0.01). Tr/ To TM value decreased significantly from 0.55±0.02 to normal value 0.48±0.02 (p<0.019). Tr/To FM index value decreased significantly from 0.56±0.02 to normal value 0.48±0.03 (p<0.033). Tr/To TM and Tr/To FM after weight loss reached normal values. Conclusions. It was confirmed that DXA indexes of central, abdominal obesity Tr/To TM and Tr/To FM were increased in overweight subjects before the weight loss and lowered significantly after the weight loss to normal values, indicating that normal BMI and BW reached after the weight loss were associated with normalized body fat distribution
Keywords: dual-energy x-rays absorptiometry; abdominal obesity; weight loss